Enhanced treatment of 2-methylpropane-2-thiol contaminated soil using magno-modified fenton process - Roohi Pejman; Fatehifar Esmaeil (Chemical Industry and Chemical Engineering Quarterly, 2020)
In this work, the nano-magno-modified Fenton process for remediation of soil polluted with 2-methylpropane-2-thiol is investigated. In this two-step oxidation process, a nanocatalyst system is used, including Fe2+/Fe3+ coupled with ethanol solvent exposed to the magnetic field. The data analysis resulting from analysis of variance shows that H2O2, NaOH, Fe3O4 nanoparticle and ethanol concentration with magnetic field intensity are effective on 2-methylpropane-2- -thiol removal efficiency (26.99, 4.36, 3.42, 17.63 and 8.66%, respectively). Moreover, H2O2/nanoFe3O4 and NaOH/nanoFe3O4 were the influencing interaction with a positive role and nanoFe3O4/ethanol, H2O2/NaOH and magnetic field/nanoFe3O4 with a negative role. The maximum level of initial H2O2 concentration, a minimum level of ethanol and certain levels of NaOH initial concentration (8.64 mass%), Fe3O4 nanoparticles to soil ratio and magnetic field intensity (0.11 mass% w/w and 3585 Oe, respectively) were suggested for the maximum contaminant remediation efficiency in the studied interval (%R = = 92.02). The magno-modified Fenton process could be used for both, increasing the removal efficiency and minimizing the vaporization of similar organosulfur compounds. Experimental results show that the solvent addition for diluting thiol contaminant could reduce the removal efficiency while the coupling of Fe3O4 and magnetic field is a good way of separation and reuse to solve the recovery problem of the nanoparticles.